Association of Pathologic Complete Response with Long-Term Survival Outcomes in Triple-Negative Breast Cancer: A Meta-Analysis - Huang, Min; O'Shaughnessy, Joyce; Zhao, Jing; Haiderali, Amin; Cortes, Javier; Ramsey, Scott D.; Briggs, Andrew; Hu, Peter; Karantza, Vassiliki; Aktan, Gursel; Qi, Cynthia Z.; Gu, Chenyang; et al. (Cancer Research, 2020)
Pathologic complete response (pCR) following neoadjuvant therapy has been associated with improved event-free survival (EFS) and overall survival (OS) in early-stage breast cancer. The magnitude of this association varies by breast cancer subtype, yet further research focusing on subtype-specific populations is limited. Here we provide an updated and comprehensive evaluation of the association between pCR and survival outcomes in triple-negative breast cancer (TNBC). A literature review identified neoadjuvant studies, including clinical trials, real-world cohort studies, and studies that pooled multiple trials or cohorts, which reported EFS/OS results by pCR in patients with early-stage TNBC. Meta-analyses were performed to evaluate the association between pCR and EFS/OS and to predict long-term survival outcomes based on pCR status. Sensitivity analyses were conducted to assess the impact of cross-study variations. Twenty-five studies with over 4,000 patients with TNBC were identified. A synthesis of evidence from these studies suggested substantial improvement in EFS and OS for pCR versus non-pCR [EFS HR (95% confidence interval): 0.24 (0.20-0.29); OS: 0.19 (0.15-0.24)]; consistent results were reported in sensitivity analyses. Collectively, our findings suggest that adjuvant therapy is associated with improved EFS/OS in patients with TNBC who received neoadjuvant therapy, regardless of pCR status.
CRIS-Team WoS Importer:2021-01-29